Damage to Pig Bile Duct Caused by Intraluminal Brachytherapy Using a 125i Ribbon. (April 2013) - Chen, Yi; Wang, Xiao-Lin; Yan, Zhi-Ping; Wang, Jian-Hua; Cheng, Jie-Min; Gong, Gao-Quan; Li, Guo-Ping
Background: Stent occlusion by tumor ingrowth or overgrowth is the main cause of jaundice recurrence after metal stent insertion in patients with malignant obstructive jaundice (MOJ). The application of intraluminal brachytherapy (ILBT) in patients with MOJ results in local control of malignant tumors, which prolong stent patency. Purpose: To evaluate the safety of ILBT in pig bile ducts using ribbons of iodine-125 ( 125 I) seeds. Material and Methods: Sixteen healthy pigs were randomly assigned to four groups of four pigs each. A 125 I seed ribbon was implanted into the common bile duct of each animal through an incision in the duct wall, and was fixed by suturing. The four groups of animals were sacrificed at 15, 30, 60, and 120 days after ribbon implantation, respectively. Serum bilirubin concentrations, alanine aminotransferase concentrations, and white blood cell counts before and after implantation were compared within each group. Pathological changes to the bile duct wall were observed using a light microscope. Morphological changes in biliary epithelial cells and organelles were observed with electron microscopy. Results: 125 I ribbons were successfully implanted in all animals without surgery-related death. We found no significant difference in pre- and post-implant serum bilirubin, alanine aminotransferase, or white blood cell counts. Light and electron microscopy showed that the most severe bile duct damage occurred in the 15-day group, which exhibited necrosis and detachment of numerous epithelial cells, and infiltration of inflammatory cells. Repair and proliferation of the bile duct epithelium began 30 days after implantation and was nearly complete at 60 days. Conclusion: This study demonstrated the safety of ILBT using a 125 I ribbon in the pig bile duct. 125 I seed ribbons may be used in the treatment of MOJ in humans.